'Kim Davis be like … ': a feminist critique of gender humor in online political memes. Issue 7 (6th June 2020) - Harlow, Summer; Rowlett, Jerrica Ty; Huse, Laura-Kate
ABSTRACT: In this era of participatory and social media, memes have become a user-generated form of political discussion. The online conversation surrounding Kentucky county clerk Kim Davis who was jailed for refusing to issue gay marriage licenses provides insight into the rhetoric used in political memes. Through qualitative and quantitative analysis using a lens of feminist humor theory, this study of Davis-related memes suggests that users trying to battle anti-gay ideologies resorted to anti-feminist rhetoric by targeting her physical appearance as a woman and using traditional 'slut humor.' Additionally, civil rights comparisons illustrate a misconstrued understanding of race and hegemony. Thus, far from serving as an alternative public sphere for marginalized voices, we conclude Internet memes are maintaining the status quo, furthering gendered political and communications systems and virtually ignoring the underlying gay rights issue.